Bromelain immobilization on microbial and animal source chitosan films, plasticized with glycerol, for application in wine-like medium: Microstructural, mechanical and catalytic characterisations. (March 2015) - Zappino, M.; Cacciotti, I.; Benucci, I.; Nanni, F.; Liburdi, K.; Valentini, F.; Esti, M.
Abstract: Films of chitosan from two different sources, microbial ( Aspergillus niger ) and animal (shell fish, providing three different molecular weights), were prepared by a solvent casting technique, and then characterised and tested for use as a covalently linked bromelain carrier in wine-like medium. Membrane morphology, microstructure, thermal and mechanical properties were investigated, showing that glycerol addition increases elongation at break and reduces tensile strength. Films based on low molecular weight chitosan blended with 25% glycerol, showed the best balance between stress strain and flexibility. The highest bromelain immobilization yield (41%) was observed on A. niger chitosan blended with glycerol, 25%, whereas for all shell fish chitosan membranes it appeared lower (27–33%). With regard to the proteolytic properties of immobilized bromelain measured towards a tripeptide chromogenic substrate, the enzyme immobilized on neat low molecular weight chitosan films turned out to be the most efficient biocatalyst in terms of maximum velocity of the enzyme-catalyzed reaction ( V max ) and the Michaelis–Menten constant (KM ). Nevertheless, taking into account both mechanical and kinetic properties, low molecular weight chitosan blended with 25% glycerol should be considered the most suitable for application in wine-making. Graphical abstract: Highlights: Films based on microbial chitosan have been obtained for the first time. Bromelain covalently linked on chitosan films resulted active in acidic medium. Low molecular weight chitosan film was the most suitable in winemaking application.